(untitled) (Psychology Travelogs, 2025)
The article addresses the issue of the development of sensitivity as a complex moral and psychological trait in adolescents, particularly in the context of emotional intelligence and socialization. The relevance of the study is determined by contemporary socio-cultural changes, including the influence of digital communication, the fast pace of life, and the rise of bullying in educational environments. Emphasis is placed on the importance of sensitivity for reducing aggression, improving interpersonal relationships, and the harmonious development of adolescents’ personalities. The theoretical foundations of empathy and sensitivity are explored, highlighting their differences, with sensitivity being defined as a category realized through communication and directly manifested in interactions with others. The study emphasizes the age-related psychological characteristics of sensitivity formation in adolescents and the significance of the senior school age as a sensitive period. Empirical research revealed that the level of sensitivity among adolescents ranges from high to low. The following indicators are defined as criteria for assessing the level of development of adolescents’ sensitivity: the ability to adequately understand nonverbal behavior, the level of development of empathy, the development of acceptance of another person, friendliness, tact, politeness, and caring. Key components of sensitivity (cognitive, emotional, and behavioral) were identified, and the levels of development of this trait were determined. Adolescents with high levels of sensitivity demonstrate active empathy and social sensitivity, while those with low levels have limited ability to recognize others’ emotions. The study’s findings underline the importance of implementing social-psychological training and educational programs to develop sensitivity in schoolchildren, as well as the need for further research into the factors influencing the development of sensitivity during adolescence.